KINERJA BIROKRASI DALAM PEMBERIAN PELAYANAN PUBLIK KEPADA MASYARAKAT PADA KANTOR KELURAHAN MALUNDA KECAMATAN MALUNDA KABUPATEN MAJENE - Munawi Gay; Eka Adriana (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to determine the performance of the bureaucracy in providing public services to the community at the Malunda Kelurahan office, Malunda Subdistrict, Majene Regency. Research using qualitative descriptive methods. Data collection through interview techniques, observation, and documentation. The results showed that the use of ADD in the preparation of development work plans was less than optimal. Village fund management from the context of planning, supervision and transparency as well as its impact on the community has been well implemented, but it is still not fully in line with community expectations even though in the preparation of village development planning the community involvement is quite good. Constraints found include; disbursement of funds is not timely, so the implementation is also delayed; frequent changes of management and workers so that the implementation of work is disrupted.